International student support and engagement in higher education exploring innovative practices in campus, academic and professional support services - Mohamed, Mutiara; Boyd, Janet 1967- (Routledge studies in global student mobility, 2023)
"International Student Support and Engagement in Higher Education examines innovative practices in campus, academic, and professional support services which serve the various and unique needs of international students seeking undergraduate and graduate degrees. Divided into three sections pertaining to campus, academic and professional support services, the authors present case studies and original research that examine strategies for how institutions of higher education can operate to promote international student success beyond the classroom. The international range of contributors showcase research from across Canada, China, Indonesia, Malaysia, Russia, Senegal, Thailand and the US. Foregrounding support services with innovative and successful methods for collaborating with one another, the book crucially addresses how the myriad support services available on campuses can work together to support international students and foster a sense of belonging and connection, rather than maintaining a focus on acculturation. It examines the origins of these partnerships, asking whether the services are designed to support the international student community specifically, or to serve the student population more generally. Identifying new emerging trends and with a view to establishing a broad and global context for best practices in international student support, this book will appeal to faculty, researchers, scholars, and scholar-practitioners with interests in higher education, student support services and international and comparative education"--